Caveolin-Mediated Endocytosis: Bacterial Pathogen Exploitation and Host–Pathogen Interaction - Dibyasri Barman; Rishi Drolia (Cells)
Within mammalian cells, diverse endocytic mechanisms, including phagocytosis, pinocytosis, and receptor-mediated endocytosis, serve as gateways exploited by many bacterial pathogens and toxins. Among these, caveolae-mediated endocytosis is characterized by lipid-rich caveolae and dimeric caveolin proteins. Caveolae are specialized microdomains on cell surfaces that impact cell signaling. Caveolin proteins facilitate the creation of caveolae and have three members in vertebrates: caveolin-1, caveolin-2, and caveolin-3. Many bacterial pathogens hijack caveolin machinery to invade host cells. For example, the Gram-positive facultative model intracellular bacterial pathogen Listeria monocytogenes exploits caveolin-mediated endocytosis for efficient cellular entry, translocation across the intestinal barrier, and cell–cell spread. Caveolin facilitates the internalization of group A streptococci by promoting the formation of invaginations in the plasma membrane and avoiding fusion with lysosomes, thereby aiding intracellular survival. Caveolin plays a crucial role in internalizing and modulation of host immune responses by Gram-negative bacterial pathogens, such as Escherichia coli K1, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Salmonella enterica serovar Typhimurium. Here, we summarize how bacterial pathogens manipulate the host’s caveolin system to facilitate bacterial entry and movement within and between host cells, to support intracellular survival, to evade immune responses, and to trigger inflammation. This knowledge enhances the intervention of new therapeutic targets against caveolin in microbial invasion and immune evasion processes.